Pelatihan Media Digital dan AI untuk Peningkatan Kapasitas Komunikasi Guru Sekolah Minggu GKJ se-Klasis Yogyakarta Barat - Melati Tobing; Marshelia Gloria Narida; Sunengsih Simatupang; Gunawan Tambunsaribu; Rachel Dina (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2026)
This community service activity aimed to enhance the communication capacity of Sunday School teachers in the GKJ West Yogyakarta Classis in responding to digital and artificial intelligence challenges. Changes in the digital communication ecosystem and children’s learning behavior required Sunday School teachers to develop adaptive communication skills, digital literacy, and ethical awareness grounded in Christian values. The activity was conducted using a participatory and educational workshop approach, consisting of counseling sessions, training, interactive discussions, and hands-on practice in utilizing digital media and AI-based applications. Evaluation was carried out through pre-test and post-test instruments to measure participants’ understanding, supported by observation of participation and practical outputs. The results showed a significant improvement in participants’ understanding, with the average score increasing from 85.33 in the pre-test to 96.57 in the post-test and an N-gain value of 0.766, categorized as high. In addition, participants were able to produce more creative and contextual teaching materials based on visual storytelling. This activity positively contributed to strengthening the role of Sunday School teachers as relevant, creative, and responsible communicators of faith in the digital era.